A kind of water-soluble flavor micro-explosive beads and preparation method thereof

By using the water-based spice bead structure composed of core material, transition layer and hydrophobic wall material, the problems of oozing and storage stability in the existing water-soluble system beads are solved, and long-term stable embedding and easy pinching of spices are achieved. Break release effect.

CN115486557BActive Publication Date: 2025-02-18CHINA TOBACCO GUANGXI IND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211293114.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-21
Publication Date
2025-02-18
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

The existing water-soluble blasting beads have problems such as oozing, dissipation, and failure to break the wall material, making it difficult to effectively enclose water-based fragrances and achieve controllable release.

Method used

A burst bead structure consisting of a core material, a transition layer and a wall material, wherein the core material is a water-soluble fragrance, water, sodium alginate, a film-forming agent and a film-forming filler, and the transition layer is made of in-situ polymerization of amphoteric monomers The amphoteric polymer material, the wall material is a hydrophobic organic polymer material prepared by in-situ copolymerization of hydrophobic monomers and hydrophobic crosslinking agents.

Benefits of technology

It effectively solves the problems of water-based spices' ooze and storage stability. The wall material is easy to pinch and releases spices without odor, and the storage stability reaches 99.5% and above 90.9%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003902092500000021
    Figure BDA0003902092500000021
  • Figure BDA0003902092500000031
    Figure BDA0003902092500000031
  • Figure BDA0003902092500000111
    Figure BDA0003902092500000111
Patent Text Reader

Abstract

The present invention discloses a water-soluble fragrance micro-explosive bead and a preparation method thereof, comprising a core material, a wall material and a hydrophobic modified material, wherein the core material is a water-based fragrance, and an aqueous solution is dripped into an aqueous solution containing a film-forming agent and a film-forming filler to form an original explosive bead; the explosive bead is sequentially immersed in an initiator aqueous solution and an amphoteric monomer, and then suspended in a heavy oil solvent to initiate polymerization of the amphoteric monomer to form a flexible wall material transition layer; a hydrophobic monomer is dripped and polymerized to form a hydrophobic layer to construct a brittle wall material outer layer. After washing, solvent removal and drying, a dense explosive bead is obtained, wherein the water-soluble fragrance is the core material, the amphoteric polymer is the transition layer, and the hydrophobic polymer is the outer layer of the wall material. The present invention prepares a wall material composed of a double-layer polymer by a one-step polymerization method, which can effectively embed water-based fragrances, is not easy to seep out, and has long-term storage stability. The wall material of the explosive bead is easy to crush and the fragrance is quickly released, and the explosive bead has no odor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of water-soluble flavoring bursting beads for cigarettes, and in particular to water-soluble flavoring micro bursting beads and a preparation method thereof. Background Art

[0002] The popping bead is a product that uses polymer materials to wrap various tobacco flavors in the form of solid, liquid or gas in a tiny, sealed spherical popping bead. One or more easily crushable flavor popping beads are implanted during the production process of the filter tip to achieve artificially controllable release of characteristic flavors during cigarette smoking, reduce the impact of the external environment on the taste and the loss of flavor, and can achieve the function of enhancing the flavor of cigarettes and enriching the taste level. At the same time, it can increase the humidity of smoke and improve the effect of filter rods to intercept aroma. The popping bead consists of two parts: wall material and core material. The wall material is made of polymer materials, plasticizers and water as raw materials, and is obtained by adjusting the proportion. It has suitable elasticity and strength, mainly plays a sealing role, and has the effects of hardness, crispness, and sound. The core material is a liquid or suspension that is insoluble in the wall material, usually an oily liquid, mainly tobacco flavors and spices. When used, it does not require pyrolysis, and the flavor components can be delivered to consumers by squeezing and breaking the wall.

[0003] The contents of the popping beads on the market are mainly composed of long-chain ester-soluble solvents and non-polar aroma substances. The packaging system used is a water-phase-wrapped oil-phase system. Generally, sodium alginate is used as the wall material, and the oil-soluble flavor popping beads are prepared mainly by the drip method. The popping bead system for cigarettes that can effectively embed water-soluble flavors is not yet mature. Invention patent CN103815541 A discloses a three-layer water popping bead for cigarettes and a preparation method thereof. The popping bead shell has two layers, the inner layer is a sodium alginate complex, and the outer layer is a wax material; invention patent CN103815542B discloses a four-layer water popping bead for cigarettes and a preparation method thereof. The popping bead shell has three layers, the inner layer is a sodium alginate complex, the inner two layers are a wax material, and the outer layer is a sodium alginate complex again. Patent CN107713008 A discloses a non-animal tobacco popping bead wall material and preparation method for wrapping water-soluble flavors. The inner layer of the popping bead is a special hot melt adhesive material. After the special hot melt adhesive is heated to a molten state. The water-soluble system popping beads currently studied are usually prepared by a physical composite method, which has problems such as leakage and loss of contents, the wall material cannot be broken by pinching, and odor. Summary of the invention

[0004] The first technical problem to be solved by the present invention is to provide a bursting bead that can encapsulate water-based fragrances for a long time and can be released by pinching, in view of the current technical status of the existing water-soluble bursting beads, such as leakage and loss of contents and the inability to break the wall material. The bursting bead of the present invention is composed of a core material, a transition layer and a wall material, wherein the core material is a water-soluble fragrance, water, sodium alginate, a film-forming agent and a film-forming filler, the transition layer is an amphiphilic polymer material formed by in-situ polymerization of amphiphilic monomers, and the wall material is a hydrophobic organic polymer material formed by in-situ polymerization of hydrophobic monomers and a hydrophobic crosslinking agent.

[0005] Preferably, the present invention provides a method for preparing water-based flavoring beads, comprising the following steps:

[0006] 1. Mix spices, water, sodium alginate, etc. in a certain ratio to prepare an aqueous solution.

[0007] 2. Mix the film-forming agent and the film-forming filler to form an aqueous solution;

[0008] 3. Slowly add the gel from step 1 to step 2 to form original explosive beads;

[0009] 4. Soak the original explosive beads in the initiator aqueous solution, take them out and put them in the solvent;

[0010] 5. Use a peristaltic pump to drop the amphoteric monomer and cross-linking agent into the original bead solvent in step 4, initiate polymerization under ultraviolet light, and form a transition layer around the bead. Continue to add hydrophobic monomer and hydrophobic cross-linking agent for polymerization to form a brittle and dense outer layer of the wall material.

[0011] The technical solution adopted by the present invention to solve the first technical problem is: a water-based flavor capsule, characterized in that it comprises the following components by weight:

[0012]

[0013]

[0014] The capsule diameter can be controlled between 0.1mm and 10mm, preferably between 2 and 5mm.

[0015] Preferably, the aqueous flavor in step 1 is one or a combination of plant extracts, food flavor substances, water-soluble polysaccharides, propylene glycol, glycerol, honey, sodium chloride, potassium sorbate or potassium citrate, alkaloids, volatile oils, tannins, sugars, amino acids, proteins, enzymes, and organic acids.

[0016] Step 2: The film-forming agent is a divalent or trivalent metal ion salt, including but not limited to one or more metal salts of iron, copper, magnesium, calcium, zinc, aluminum, etc.

[0017] Step 2: The film-forming filler includes, but is not limited to, one or more of starch, dextrin, cyclodextrin, and sodium carboxymethyl cellulose.

[0018] The water-soluble and oil-soluble initiators described in step 4 mainly include Irgacure series and 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP); azo compounds include azobisisobutylamidine hydrochloride (AI BA, V-50 initiator), azobisisobutylimidazoline hydrochloride (abbreviated as AIBI, VA-044 initiator), azobiscyanovaleric acid (abbreviated as ACVA, V-501), and azobisisopropylimidazoline (abbreviated as AIP, VA-061 initiator); the redox initiator includes any one of the Irgacure series and 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) and any one of organic compounds such as alcohols, amines, oxalic acid and glucose hydroperoxide.

[0019] Preferably, the transition layer described in step 5 is polymerized by initiating polymerization under ultraviolet light with the initiator described in step 4 by at least one amphoteric monomer selected from carboxyl, hydroxyl, epoxy-modified butadiene, isoprene, styrene, and myrcene, and any combination of two or three of the monomers.

[0020] Preferably, the peristaltic pump droplet speed in step 5 is 0.2-1.5 mL / min.

[0021] Preferably, the wavelength of the ultraviolet light in step 5 is 250-320 nm, and the ultraviolet power is 15 watts-120 watts.

[0022] Preferably, the wall material in step 5 is a binary or higher copolymer of any combination thereof copolymerized in a solvent by at least one of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, n-pentyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, pentyl acrylate, methyl epoxy acrylate, ethyl epoxy acrylate, and propyl epoxy acrylate and a crosslinking agent of diethylene glycol bis(methacrylate), triethylene glycol bis(methacrylate), α,ω-dimethacrylate-based polyethylene glycol, PEG diacrylate (molecular weight 400-5000), glycerol trimethyl acrylate, glycerol trimethyl methacrylate, pentaerythritol tetramethacrylate, and pentaerythritol tetraacrylate.

[0023] Step 4 and step 5 are the same solvent, which includes but is not limited to any one of silicone oil (density greater than water), aliphatic hydrocarbon oil (density greater than water), ethylene oxide propylene oxide copolymer (molecular weight 400-5000), PEG (molecular weight 400-5000) and any one or more of n-hexane, n-octane, cyclohexane, isooctane, and n-heptane.

[0024] Compared with the existing water-based fragrance system, the advantages of the present invention are:

[0025] 1. The wall material and the core material are connected by a transition layer. The transition layer is an organic polymer material prepared in situ from amphiphilic monomers. It has polar-polar chemical reaction with the hydrophilic core material and strong covalent bond with the hydrophobic wall material. It has good interfacial compatibility with both materials, thus solving the problem of core material loss caused by interface shedding between the core material and the wall material in the current water-based fragrance system.

[0026] 2. The wall material is prepared by in-situ copolymerization of hydrophobic monomers and hydrophobic crosslinking agents outside the transition layer. It has a dense texture and strong hydrophobicity. The water-based fragrance in the core material is not easy to seep out, and the long-term storage stability of 30 days and 60 days reaches more than 99.5% and 90.9% respectively;

[0027] 3. The bead wall material is easy to crush and the spices can seep out and be released quickly;

[0028] 4. The popping beads have no peculiar smell. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the embodiments.

[0030] Embodiment 1:

[0031] 10 g of aqueous fragrance and 0.15 g of sodium alginate were dissolved in 1.5 g of water to prepare aqueous solution 1. 8.25 g of film-forming agent calcium chloride and 0.2 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 1.0 wt-% aqueous solution of aqueous initiator Irgacure for 30 minutes, and then suspended in silicone oil. Subsequently, 12 mL of silicone oil solution containing hydroxymyrcene (concentration 10.0%) was added dropwise at a rate of 0.3 mL / min using a peristaltic pump, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 72 W ultraviolet light was used to initiate the polymerization of the monomers for 5 hours to form a transition layer, and then 50 mL of silicone oil solution containing 5.0 g of methyl methacrylate and 1.0 g of PEG diacrylate was added dropwise at a rate of 1.0 mL / min using a peristaltic pump, and polymerized for 6 hours under slow stirring to form a wall material, and the beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0032] Embodiment 2:

[0033] 10 g of aqueous fragrance and 0.29 g of sodium alginate were dissolved in 3.6 g of water to prepare aqueous solution 1. 11.21 g of film-forming agent calcium chloride and 0.4 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 0.5 wt-% aqueous solution of an aqueous initiator Irgacure for 25 minutes, and then suspended in silicone oil. Subsequently, a peristaltic pump was used to drop 3 mL of a silicone oil solution containing hydroxymyrcene (concentration 8.0%) at a speed of 0.2 mL / min, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 45 w ultraviolet light was used to initiate the polymerization of the monomers for 1.5 hours to form a transition layer, and then a peristaltic pump was used to drop 30 mL of a silicone oil solution containing 4.5 g of methyl methacrylate and 1.2 g of PEG diacrylate at a speed of 0.9 mL / min, and the wall material was formed by slowly stirring and polymerizing for 4 hours. The beads were washed with n-hexane, alcohol and water, respectively, and dried naturally. The properties are shown in Table 1.

[0034] Embodiment 3:

[0035] 10 g of aqueous fragrance and 0.56 g of sodium alginate were dissolved in 20 g of water to prepare aqueous solution 1. 14.39 g of film-forming agent calcium chloride and 0.6 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 1.5 wt-% aqueous solution of an aqueous initiator Irgacure for 35 minutes, and then suspended in silicone oil. Subsequently, a peristaltic pump was used to drop 10 mL of a silicone oil solution containing hydroxymyrcene (concentration 6.0%) at a rate of 0.5 mL / min, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 24 w ultraviolet light was used to initiate the polymerization of the monomers for 5 hours to form a transition layer. A peristaltic pump was then used to drop 18 mL of a silicone oil solution containing 10.0 g of methyl methacrylate and 2.0 g of PEG diacrylate at a rate of 0.5 mL / min, and the wall material was formed by slowly stirring and polymerizing for 4 hours. The beads were washed with n-hexane, alcohol and water, respectively, and dried naturally. The properties are shown in Table 1.

[0036] Embodiment 4:

[0037] 10 g of aqueous flavor and 0.32 g of sodium alginate were dissolved in 1.8 g of water to prepare aqueous solution 1. 8.25 g of film-forming agent calcium chloride and 0.2 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel balls. The balls were soaked in a 1.5 wt-% aqueous solution of aqueous initiator HMPP for 30 minutes, and then suspended in silicone oil. Subsequently, a peristaltic pump was used to drop 3 mL of a silicone oil solution containing hydroxymyrcene (concentration 5.0%) at a speed of 0.2 mL / min, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w ultraviolet light was used to initiate the polymerization of the monomers for 2.5 hours to form a transition layer, and then a peristaltic pump was used to drop 30 mL of a silicone oil solution containing 2.0 g of methyl methacrylate and 0.5 g of PEG diacrylate at a speed of 0.3 mL / min, and the wall material was formed by slowly stirring and polymerizing for 4 hours. The beads were washed with n-hexane, alcohol and water, respectively, and dried naturally. The properties are shown in Table 1.

[0038] Embodiment 5:

[0039] 10 g of aqueous flavor and 0.39 g of sodium alginate were dissolved in 40 g of water to prepare aqueous solution 1. 8.25 g of film-forming agent calcium chloride and 0.2 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 1.0 wt-% aqueous solution of aqueous initiator HMPP for 60 minutes, and then suspended in silicone oil. Subsequently, 7 mL of silicone oil solution containing hydroxymyrcene (concentration 7.0%) was added dropwise at a rate of 0.2 mL / min using a peristaltic pump, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w ultraviolet light was used to initiate the polymerization of the monomers for 2.0 hours to form a transition layer, and then 30 mL of silicone oil solution containing 4.0 g of methyl methacrylate and 1.0 g of PEG diacrylate was added dropwise at a rate of 0.8 mL / min using a peristaltic pump, and polymerized for 8 hours under slow stirring to form a wall material. The beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0040] Embodiment 6:

[0041] 10 g of aqueous fragrance and 0.19 g of sodium alginate were dissolved in 1.1 g of water to prepare aqueous solution 1. 12.25 g of film-forming agent calcium chloride and 0.2 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 1.5 wt-% aqueous solution of aqueous initiator Irgacure for 45 minutes, and then suspended in silicone oil. Subsequently, a peristaltic pump was used to drop 20 mL of a silicone oil solution containing epoxymyrcene (concentration 10.0%) at a speed of 0.2 mL / min, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w ultraviolet light was used to initiate the polymerization of the monomers for 5.0 hours to form a transition layer, and then a peristaltic pump was used to drop 40 mL of a silicone oil solution containing 6.0 g of methyl methacrylate and 1.8 g of PEG diacrylate at a speed of 1.2 mL / min, and the wall material was formed by slowly polymerizing for 8 hours under stirring. The beads were washed with n-hexane, alcohol and water, respectively, and dried naturally. The properties are shown in Table 1.

[0042] Embodiment 7:

[0043] 10 g of aqueous fragrance and 0.25 g of sodium alginate were dissolved in 1.9 g of water to prepare aqueous solution 1. 8.25 g of film-forming agent calcium chloride and 0.16 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 2.5 wt-% aqueous solution of an aqueous initiator Irgacure for 45 minutes, and then suspended in silicone oil. Subsequently, a 20 mL silicone oil solution containing epoxymyrcene (concentration 10.0%) was added dropwise at a rate of 0.2 mL / min using a peristaltic pump, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w ultraviolet light was used to initiate the polymerization of the monomers for 4.0 hours to form a transition layer, and then a 20 mL silicone oil solution containing 7.0 g methyl acrylate and 1.2 g cross-linking agent pentaerythritol tetramethacrylate was added dropwise at a rate of 1.2 mL / min using a peristaltic pump, and slowly stirred for polymerization for 8 hours to form a wall material, and the beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0044] Embodiment 8:

[0045] 10 g of aqueous flavor and 0.55 g of sodium alginate were dissolved in 3.7 g of water to prepare aqueous solution 1. 9.25 g of film-forming agent calcium chloride and 0.36 g of film-forming filler chitosan were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 5.5 wt-% aqueous solution of aqueous initiator HMPP for 60 minutes, and then suspended in a silicone oil n-hexane solution. Subsequently, 10 mL of silicone oil / 5 mL of n-hexane containing epoxymyrcene (concentration 10.0%) was added dropwise at a rate of 0.3 mL / min using a peristaltic pump. After slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w of ultraviolet light was used to initiate the polymerization of the monomers for 3.5 hours to form a transition layer. Then, a 25 mL of silicone oil / 5 mL of n-hexane solution containing 10.0 g of methyl acrylate and 1.9 g of a cross-linking agent pentaerythritol tetramethacrylate was added dropwise at a rate of 1.5 mL / min using a peristaltic pump. The solution was slowly polymerized for 6 hours under stirring to form a wall material. The beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0046] Embodiment 9:

[0047] 10 g of aqueous flavor and 0.78 g of sodium alginate were dissolved in 5.2 g of water to prepare aqueous solution 1. 7.01 g of film-forming agent calcium chloride and 0.32 g of film-forming filler chitosan were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 2.2 wt-% aqueous solution of an aqueous initiator Irgacure for 60 minutes, and then suspended in a silicone oil n-octane solution. Subsequently, a 10 mL silicone oil / 2 mL n-octane solution containing epoxymyrcene (concentration 8.0%) was added dropwise at a rate of 0.3 mL / min using a peristaltic pump, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 45 w ultraviolet light was used to initiate the polymerization of the monomers for 3.5 hours to form a transition layer, and then a 10 mL silicone oil / 2 mL n-octane solution containing 9.0 g methyl acrylate and 2.0 g cross-linking agent pentaerythritol tetramethacrylate was added dropwise at a rate of 1.1 mL / min using a peristaltic pump, and the wall material was formed by slowly stirring and polymerizing for 3.5 hours. The beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0048] Embodiment 10:

[0049] 10 g of aqueous flavor and 0.93 g of sodium alginate were dissolved in 10 g of water to prepare aqueous solution 1. 14.95 g of film-forming agent calcium chloride and 0.23 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were immersed in 6.5 wt-% aqueous initiator HMPP and stirred, then fished out and suspended in silicone oil n-octane solution. Subsequently, a 12 mL silicone oil / 1 mL n-octane solution containing epoxymyrcene (concentration 12.0%) was added dropwise at a rate of 0.3 mL / min using a peristaltic pump. After slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w ultraviolet light was used to initiate the polymerization of the monomers for 3.5 hours to form a transition layer. Then, a 12 mL silicone oil / 1 mL n-octane solution containing 12.0 g methyl methacrylate and 1.7 g cross-linking agent pentaerythritol tetramethacrylate was added dropwise at a rate of 1.2 mL / min using a peristaltic pump. The solution was slowly polymerized for 4 hours under stirring to form a wall material. The beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0050] Embodiment 11:

[0051] 10 g of aqueous fragrance and 1.41 g of sodium alginate were dissolved in 20 g of water to prepare aqueous solution 1. 8.25 g of film-forming agent calcium chloride and 0.18 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 3.5 wt-% aqueous solution of aqueous initiator Irgacure for 26 minutes, and then suspended in a silicone oil n-octane solution. Subsequently, a 10 mL silicone oil / 2 mL n-octane solution containing epoxymyrcene (concentration 8.0%) was added dropwise at a rate of 0.5 mL / min using a peristaltic pump. After slowly stirring to ensure that the beads were suspended and not bonded to each other, 36 w ultraviolet light was used to initiate the polymerization of the monomers for 3.5 hours to form a transition layer. Then, a 10 mL silicone oil / 2 mL n-octane solution containing 12.0 g methyl methacrylate and 2.1 g cross-linking agent propylene glycol trimethacrylate was added dropwise at a rate of 1.5 mL / min using a peristaltic pump. The solution was slowly polymerized for 4 hours under stirring to form a wall material. The beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0052] Comparative Example 1:

[0053] 10g of water-based fragrance and 0.42g of sodium alginate were dissolved in 1.8g of water to prepare aqueous solution 1, 8.25g of film-forming agent calcium chloride and 0.18g of film-forming filler cyclodextrin were dissolved in 100g of aqueous solution to prepare solution 2, solution 1 was slowly added to solution 2 with a dropper to form gel beads, the beads were soaked in a 3.5wt-% aqueous solution of water-based initiator Irgacure for 60 minutes, and then suspended in a silicone oil n-octane solution after being fished out. 8.0g of methyl acrylate and 1.6g of cross-linking agent pentaerythritol tetramethacrylate in 12mL silicone oil / 2mL n-octane solution were added dropwise with a peristaltic pump at a speed of 1.4mL / min, and polymerized for 4 hours under slow stirring to form wall materials, and the beads were washed with n-hexane, alcohol and clean water respectively, and dried naturally. The properties are shown in Table 1.

[0054] Comparative Example 2:

[0055] 10g of water-based fragrance and 0.35g of sodium alginate were dissolved in 2.1g of water to form aqueous solution 1, 8.25g of film-forming agent calcium chloride and 0.16g of film-forming filler chitosan were dissolved in 100g of aqueous solution to form solution 2, solution 1 was slowly added dropwise to solution 2 with a dropper to form gel beads, the beads were soaked in an aqueous solution of 5.5wt% of water-based initiator HMPP for 60 minutes, and then suspended in silicone oil after being fished out. Subsequently, 10mL of silicone oil solution containing epoxymyrcene (concentration 8.0%) was added dropwise with a peristaltic pump at a speed of 0.5mL / min, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 36w ultraviolet light was used to initiate monomer polymerization for 3.5 hours to form a transition layer, and the beads were washed with n-hexane, alcohol and clean water respectively, and dried naturally. The properties are shown in Table 1.

[0056] Embodiment 3:

[0057] 10 g of aqueous fragrance and 1.41 g of sodium alginate were dissolved in 2.1 g of water to prepare aqueous solution 1. 8.25 g of film-forming agent calcium chloride and 0.18 g of film-forming filler cyclodextrin were dissolved in 100 g of aqueous solution to prepare solution 2. Solution 1 was slowly added to solution 2 with a dropper to form gel beads. The beads were soaked in a 3.5 wt-% aqueous solution of aqueous initiator Irgacure for 21 minutes, and then suspended in silicone oil. Subsequently, a peristaltic pump was used to drop 10 mL of a silicone oil solution containing epoxymyrcene (concentration 8.0%) at a rate of 1.1 mL / min, and after slowly stirring to ensure that the beads were suspended and not bonded to each other, 72 W ultraviolet light was used to initiate the polymerization of the monomers for 4 hours to form a transition layer. A peristaltic pump was then used to drop 12.0 g of methyl methacrylate in 10 mL of a silicone oil solution at a rate of 1.5 mL / min, and the beads were slowly polymerized for 4 hours under slow stirring to form a wall material. The beads were washed with n-hexane, alcohol and clean water, respectively, and dried naturally. The properties are shown in Table 1.

[0058] Table 1: Bead bursting performance

[0059]

[0060] The present invention prepares a wall material composed of a double-layer polymer by a one-step polymerization method, can effectively embed water-based fragrances, is not easy to seep out, and has long-term storage stability. The wall material of the popping beads is easy to crush and the fragrance is quickly released, and the popping beads have no odor.

Claims

1. A method for preparing water-soluble flavor micro-explosive beads, characterized in that: The method comprises the following steps: (1) Mix 8-90 parts by weight of fragrance, 3-60 parts by weight of water, and 0.5-5 parts by weight of sodium alginate to prepare aqueous solution 1; (2) mixing 0.01-0.05 parts by weight of calcium chloride as a film-forming agent and 0.01-0.05 parts by weight of cyclodextrin as a film-forming filler to prepare a 0.1-5 wt% aqueous solution 2; (3) slowly adding aqueous solution 1 to aqueous solution 2 to form original explosive beads; (4) soaking the original explosive beads in a 0.5-2.0 wt % aqueous solution of the initiator Irgacure; (5) The original popping beads soaked in step (4) are fished out, soaked in silicone oil, and a silicone oil solution of hydroxymyrcene or epoxymyrcene amphiphilic monomers is slowly injected using a peristaltic pump to initiate polymerization under ultraviolet light to form a flexible transition layer of wall material around the popping beads; methyl methacrylate or methyl acrylate hydrophobic monomers and cross-linking agents PEG diacrylate, pentaerythritol tetramethacrylate or propylene glycol trimethacrylate are continuously added for copolymerization to form a brittle and dense outer layer of the wall material.

2. The method according to claim 1, wherein the ultraviolet light wavelength described in step (5) is 250-320 nm, and the ultraviolet power is 15 watts-120 watts.

3. The method according to claim 1, wherein the peristaltic pump dripping speed in step (5) is 0.2-1.5 mL / min.

Citation Information

Patent Citations

  • Water capsule for three-layer cigarette and preparation method of water capsule

    CN103815541A

  • Non-animal ice blast wall material capable of wrapping water-soluble essence and preparation method

    CN107713008A

  • Four-layer water-for-cigarette capsule and preparation method thereof

    CN103815542B

  • Water-bearing capsule and preparation method thereof

    CN104726199A

  • Preparation method of composite encapsulation capsules for cigarettes

    CN104893827A